You are missing information in some cases.
1) You need to know the function f(x) and replace x by -2
Ex: f(x)=x+2 then f(-2) = -2+2=0
2) You need to know the function f(x) and replace x by -4
Ex: f(x)=x+2 then f(-4)= -4+2 = -2
3) You have all the information:
(f-g)(x) = f(x) - g(x) = 2x-3 - (4x+8)
= 2x -3 - 4x - 8 changing the signs inside the parenthesis
= (2x - 4x) + (-3 - 8) Regrouping
= -2x + (-11 ) because -a-b = - (a+b)
= -2x - 11 because +*- = -
4) You have g(x) but you need to have also f(x)
(f+g)(x) = f(x) + g(x) = f(x) + (-x-3) = f(x) - x - 3
15 Million Students Helped!
Sign up to view the full answer